Effects of Citrus kawachiensis Peel in Frailty-like Model Mice Induced by Low Protein Nutrition Disorders - Toshiki Omasa; Satoshi Okuyama; Atsushi Sawamoto; Mitsunari Nakajima; Yoshiko Furukawa (MDPI AG, 2023)
"Frailty" caused by a decline in physiological reserve capacity, chronic inflammation, and oxidative stress in the elderly has recently become a major social issue. The present study examined the effects of the peel of Citrus kawachiensis (CK), which exhibits anti-inflammatory, antioxidant, and pro-neurogenesis activities in frailty-like model mice. Male C57BL/6 mice (15 weeks old) were fed an 18% protein diet (CON), a 2.5% protein diet (PM), and PM mixed with 1% dried CK peel powder for approximately 1 month. Mice were euthanized 2 or 8 days after a single intraperitoneal administration of lipopolysaccharide (LPS) and tissues were dissected. Among peripheral tissues, muscle weight, liver weight, and blood glucose levels were significantly higher in the PM-LPS-CK group than in the PM-LPS group. In the behavioral analysis, locomotive activity was significantly lower in the PM-LPS group than in the PM group. The reduction in locomotive activity in the PM-LPS-CK group was significantly smaller than that in the PM-LPS group. The quantification of microglia in the hippocampal stratum lacunosum-moleculare revealed that increases in the PM-LPS group were significantly suppressed by the dried CK peel powder. Furthermore, the quantification of synaptic vesicle membrane proteins in the hippocampal CA3 region showed down-regulated expression in the PM-LPS group, which was significantly ameliorated by the administration of the dried CK peel powder. Collectively, these results suggest that CK inhibits inflammation and oxidative stress induced by PM and LPS in the central nervous system and peripheral tissue. Therefore, C. kawachiensis is highly effective against "frailty".